(untitled) (Philology, 2026)
This article outlines a methodology for studying the intercultural competence and social distance of teachers and students involved in a digital ethno-practice. The study, conducted as part of the project “Bulgaria-Central Asia: Dialogue of Cultures in a Digital Environment”, aimed to characterize these two dimensions among Bulgarian and Central Asian participants after their intercultural interaction. The authors developed a methodology inspired by the work of M. Barrett and E. Bogardus. It utilizes a detailed questionnaire that includes scales measuring values, behavioral attitudes, practical skills, and knowledge necessary for effective intercultural communication. Additionally, an educational section was included to evaluate the learning outcomes of the ethno-practice itself. The conceptual and experimental model for developing intercultural competence will be further refined by increasing the number of participants from Sofia University and its partner universities in Central Asia. The findings from this study will be used to create joint educational courses for future ethno-practices.